Peranan Wanita Pendamping Suami Menjalankan Bisnis Keluarga Dalam Pengembangan Bisnis Studi Industri Kecil Kerupuk di Tuntang Kabupaten Semarang - Linda Ariany Mahastanti; Yeterina Widi Nugrahanti (Jurnal Siasat Bisnis, 2010)
The phenomenon of women working to fulfill their families’ needs in times of economic crisis is very interesting. This research focused on women co-entrepreneur who cooperated with their husbands in running their business. This research has been undertaken in Tuntang Semarang. The method of collecting data utilized descriptive statistic with questionnaire and in-depth interview with key persons. Findings examined whereas women co-entrepreneurs have barrier to operate their business like season, raw materials, financial capital and managerial, they have motivation to work due to improving their family prosperity. Keywords: women co-entrepreneur, motivasi, peran, hambatan, tuntang